S49 The role of platelet-derived TGFβ in pulmonary fibrosis. (15th November 2016) - Chong, DLW; Rebeyrol, C; Khawaja, A; Forty, EJ; Kanda, N; Scotton, CJ; Porter, JC
Abstract : Background: Pulmonary Fibrosis (PF) is characterised by abnormal wound healing involving fibroblast proliferation, myofibroblast differentiation and increased extracellular matrix deposition. TGFβ is an important driving force in fibrotic disease, however the source of this cytokine in PF is ill-defined. Platelets can release large amounts of TGFβ, and we, and others, have shown platelet deposition in the lungs of patients with idiopathic pulmonary fibrosis (IPF), although the role of these cells in PF is unknown. Hypothesis: We propose that platelet aggregation and release of platelet-derived TGFβ contributes to the aberrant wound healing in fibroproliferative lung disease. Methods: We used a double-transgenic mouse with megakaryocytic-specific deletion of TGFβ (PF4-Cre + /Tgfb1 fl ) and hence platelets lacking TGFβ. Knockout (KO) mice and wildtype (WT) littermate controls were subjected to the experimental model of lung fibrosis induced by oropharyngeal bleomycin administration. Lung tissue and broncho-alveolar lavage fluid (BALF) were investigated at 6, 21 or 28 days post-bleomycin. Complementary in vitro studies were performed on isolated neutrophils to investigate the effects of platelet-derived TGFβ in chemotaxis assays. Results: In vitro : Platelet-derived TGFβ was shown to be a potent neutrophil chemoattractant with maximal effect at 1ng/ml. In vivo : At 6 days after bleomycin treatment, neutrophils and macrophages were significantly elevated in the lung and BALF in both WT and KO animals as measured by flow cytometric analysis. No significant difference in the percentage or total cell numbers was found between WT or KO mice. At 21 days post-bleomycin, the lungs developed large fibrotic lesions when examined by micro-CT. Bleomycin-treated KO mice exhibited an attenuated fibrotic response compared with WT animals (26.9 vs. 19.6%), although not reaching statistical significance. During the wound resolution phase at 28 days post treatment, the degree of fibrosis between WT and KO animals was very similar (9.56 vs. 9.84%) as determined by micro-CT analysis. Conclusion: Our data suggest that despite being a potent neutrophil chemoattractant in vitro, platelet-derived TGFβ in vivo is not a major driving force during the inflammatory or resolution phases of our PF animal model, but may contribute to the development of fibrotic disease. This will be the subject of further study.